TUMBUH DAN BERKEMBANGNYA PESANTREN DI INDONESIA - BAHARUDDIN, ISMAIL (FORUM PAEDAGOGIK, 2014)
Islamic education institutions grow and evolve since the advent of Islam to Indonesia, and the process of Islamization in Indonesia can not be separated from theÂ  institutions.According to the conclusion of the seminar coming of Islam to Indonesia in Medan in 1963, Islam has entered Indonesia since the first century of the Hegira, or about the seventh or eighth century AD. The first area is the Islamic attended coast of Sumatra, and the first Islamic kingdom in Aceh. The results of the seminar in the field in 1963 also strengthened by the results of the Seminar and grow Sign Islam in Aceh, which was held in 1978.When starting from the results of the seminar means that in about the 7th century and 8th AD has grown centers of Islamic education in Indonesia. Places ongoing Islamic education at the early stage centered in the mosque, mosque, meunasah, rangkang, and Boarding School. On the island of Java.Boarding School who is the "fatherâ€ of Islamic education in Indonesia, established because of the demands and needs of the times, it can be seen from its historical journey, that actually boarding born on awareness obligations Islamic propaganda, which spread and develop the teachings of Islam, as well as scoring a cadre of scholars and preachers.As an Islamic educational institutions, schools of cultural historical angle can be said to be a "training center" which automatically become "cultural central" Islam endorsed or instituted by the public, at least by the de facto Islamic society itself can not be ignored by the government.Therefore, in this paper will discuss the start of the origin of boarding, boarding school elements, growing development of boarding schools and boarding schools as institutions of Islamic education in Indonesia.